2021
DOI: 10.3389/fcell.2021.657406
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Autophagy Impacts Growth and Multicellular Development in a Dictyostelium Knockout Model of CLN5 Disease

Abstract: Mutations in CLN5 cause a subtype of neuronal ceroid lipofuscinosis (NCL) called CLN5 disease. While the precise role of CLN5 in NCL pathogenesis is not known, recent work revealed that the protein has glycoside hydrolase activity. Previous work on the Dictyostelium discoideum homolog of human CLN5, Cln5, revealed its secretion during the early stages of development and its role in regulating cell adhesion and cAMP-mediated chemotaxis. Here, we used Dictyostelium to examine the effect of cln5-deficiency on var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(67 citation statements)
references
References 108 publications
14
52
1
Order By: Relevance
“…While the mechanisms regulating autophagy-dependent secretion are not fully understood, autophagy (ATG) genes ( Box 1 ), autophagosomes ( Box 1 ) and multivesicular bodies ( Box 1 ) are thought to play important roles ( Duran et al, 2010 ; Manjithaya et al, 2010 ; Chen et al, 2017 ). Consistent with these findings, pharmacological treatment (ammonium chloride or chloroquine) or deletion of ATG genes ( atg1 − or atg9 − ) reduce Cln5 secretion in D. discoideum ( Huber and Mathavarajah, 2018b ; McLaren et al, 2021 ). In addition, the functions of D. discoideum Cln5 ( McLaren et al, 2021 ), mouse CLN5 ( Leinonen et al, 2017 ), sheep CLN5 ( Best et al, 2017 ) and human CLN5 ( Adams et al, 2019 ; Doccini et al, 2020 ) have all been linked to autophagy.…”
Section: Mechanisms That Regulate Cln5 Secretion In D Discoideumsupporting
confidence: 65%
See 2 more Smart Citations
“…While the mechanisms regulating autophagy-dependent secretion are not fully understood, autophagy (ATG) genes ( Box 1 ), autophagosomes ( Box 1 ) and multivesicular bodies ( Box 1 ) are thought to play important roles ( Duran et al, 2010 ; Manjithaya et al, 2010 ; Chen et al, 2017 ). Consistent with these findings, pharmacological treatment (ammonium chloride or chloroquine) or deletion of ATG genes ( atg1 − or atg9 − ) reduce Cln5 secretion in D. discoideum ( Huber and Mathavarajah, 2018b ; McLaren et al, 2021 ). In addition, the functions of D. discoideum Cln5 ( McLaren et al, 2021 ), mouse CLN5 ( Leinonen et al, 2017 ), sheep CLN5 ( Best et al, 2017 ) and human CLN5 ( Adams et al, 2019 ; Doccini et al, 2020 ) have all been linked to autophagy.…”
Section: Mechanisms That Regulate Cln5 Secretion In D Discoideumsupporting
confidence: 65%
“…Mfsd8 is the D. discoideum homolog of human MFSD8 ( Table 1 ) and mutations in MFSD8 cause CLN7 disease ( Box 1 ) ( Table 1 ). In addition, recent work suggests that D. discoideum Cln5 is secreted following induction of autophagy via an unconventional pathway involving the CV system ( Huber and Mathavarajah, 2018b ; McLaren et al, 2021 ) ( Fig. 2 ).…”
Section: Mechanisms That Regulate Cln5 Secretion In D Discoideummentioning
confidence: 99%
See 1 more Smart Citation
“…At a cellular level deletion of cln5 results in an increased number of autophagosomes and ubiquitinated proteins, consistent with increased autophagic activity (Figure 4B). Development in the presence of an autophagy inhibitor impaired the formation of developmental structures, including reduction in slug size (McLaren et al, 2021). These data suggest that Cln5 plays a similar role in both Dictyostelium and human biology and may play a role in autophagy.…”
Section: Cln5mentioning
confidence: 69%
“…Further investigation of Cln5 was found that cln5 − -cells have reduced cell proliferation, cytokinesis, viability, folic acid-mediated endocytosis, and growth in nutrient-limited media. cln5 − cells develop more rapidly than wild-type cells (McLaren et al, 2021). cln5 − cells also exhibit impaired spore morphology, germination, and viability.…”
Section: Cln5mentioning
confidence: 95%